The impact of cyberbullying on adolescents: social and psychological consequences from a population demography perspective in Assiut Governorate, Egypt - Muhammed, Nisreen Yachoub; Samak, Yasser Abdelazim Abdelmawgoud (Frontiers in Human Dynamics, 2025)
IntroductionCyberbullying has emerged as a pressing concern among adolescents with the increased use of the internet and social media. This study aims to investigate the prevalence and impact of cyberbullying among adolescents in Assiut Governorate, Egypt, focusing on its relationship with various demographic and psychological factors.MethodsA total of 3,361 adolescents (580 males and 2,777 females), aged 16 to 21 years, participated in the study. Data were collected using three validated instruments: the Adolescent Cyberbullying Scale, the Bully/Victim Questionnaire, and the Six-Item State Self-esteem Scale. Variables examined included age, gender, professional status, marital status, and self-esteem.ResultsThe highest prevalence of cyberbullying was observed among adolescents aged 18–19. There were no statistically significant gender differences. Professional and marital statuses showed a positive correlation with cyberbullying, suggesting increased vulnerability among socially visible individuals. Conversely, self-esteem had a negative correlation with cyberbullying but did not significantly correlate with victimization.DiscussionThe findings emphasize the urgent need for targeted interventions to mitigate cyberbullying. Promoting digital literacy, emotional resilience, and supportive environments in schools and families is crucial. The study provides practical recommendations, including integrating digital literacy programs into school curricula. Future research should further explore psychological mechanisms contributing to cyberbullying.